Revealing the relative importance among plant species, slope positions, and soil types on rhizosphere microbial communities in northern tropical karst and non-karst seasonal rainforests of China - Zhang, Xingming; Wang, Bin; Chen, Ting; Guo, Yili; Li, Xiankun (Frontiers in Microbiology, 2023)
The northern tropical seasonal rainforest is one of the global biodiversity hotspots. The study on the relationship between rhizosphere microorganisms and plants in this area is conducive to the protection of vegetation and the maintenance of biodiversity. High-throughput sequencing technology was applied to study the influences of plant species, slope positions and soil types on the rhizosphere microbial community in the northern tropical seasonal rainforest. The results indicated that soil types exerted the biggest influence on rhizosphere microbial diversity, followed by slope positions and finally plant species, which could be explained by the biogeochemical properties in the rhizosphere soil. Notably, environmental factors closely related to soil types were the major influence factors that controlling the rhizosphere bacterial community structure in the northern tropical seasonal rainforest, especially pH. Additionally, plant species also influenced the rhizosphere bacterial community. In low nitrogen content soil environments, rhizosphere biomarkers of dominant plant species were often nitrogen-fixing strains. Results suggested that plants had a selective adaptation mechanism to rhizosphere microorganisms to obtain the advantages of nutrient supply. This mechanism has a great significance to ecological restoration and agricultural production.